Sleep quality and the associated factors among undergraduate student at health campus, Universiti Sains Malaysia - Saffie, Nurul Atikah Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
It is acknowledged that sleep quality is frequently worsened in university students. Lack of awareness of the symptoms and early treatment can lead to other diseases. Thus, this study aimed to investigate the sleep quality and associated factors among undergraduate students at Health Campus USM. A total of 250 undergraduate students aged between 19 to 30 years old from the three schools (Health Science, Medicine and Dentistry) were involved in this study. A cross-sectional study design was employed. The Pittsburgh Sleep Quality Index (PSQI) and International Physical Activity Questionnaire (IPAQ) were utilized for data collection. Then the data were analyzed using SPSS version 26. Pearson Chi-Square Test was used to identify the association between socio-demographic characteristics (gender, body mass index, physical activity and sleeping pattern) with sleep quality. The majority of the respondents in this study had a poor level of sleep quality (n=203, 81.2%). Among the four factors, only gender was found to have no significant association with sleep quality (p= 0.071). While the other three factors; body mass index (p= 0.08), physical activity (p= 0.002) and sleeping pattern (p=0.001) have been found significant association with sleep quality. On the other hand, most of the undergraduate students had poor levels of sleep quality and were moderately active (n=98, 39.2%). These findings revealed, there was a need to increase university students' awareness and improve their level of sleep quality among undergraduate students as a preventive measure for further problems such as practicing sleep hygiene and include physical activity in daily routine.